OPTimising MEDicine information handover after Discharge (OPTMED-D): protocol for development of a multifaceted intervention and stepped wedge cluster randomised controlled trial - Laetitia Hattingh; Melissa T. Baysari; Holly Foot; Tin Fei Sim; Gerben Keijzers; Mark Morgan; Ian Scott; Richard Norman; Faith Yong; Barbara Mullan; Claire Jackson; Leslie E. Oldfield; et al. (Trials)
Abstract Background General practitioners (GP) and community pharmacists need information about hospital discharge patients’ medicines to continue their management in the community. This necessitates effective communication, collaboration, and reliable information-sharing. However, such handover is inconsistent, and whilst digital systems are in place to transfer information at transitions of care, these systems are passive and clinicians are not prompted about patients’ transitions. There are also gaps in communication between community pharmacists and GPs. These issues impact patient safety, leading to hospital readmissions and increased healthcare costs. Methods A three-phased, multi-method study design is planned to trial a multifaceted intervention to reduce 30-day hospital readmissions. Phase 1 is the co-design of the intervention with stakeholders and end-users; phase 2 is the development of the intervention; phase 3 is a stepped wedge cluster randomised controlled trial with 20 clusters (community pharmacies). Expected intervention components will be a hospital pharmacist navigator, primary care medication management review services, and a digital solution for information sharing. Phase 3 will recruit 10 patients per pharmacy cluster/month to achieve a sample size of 2200 patients powered to detect a 5% absolute reduction in unplanned readmissions from 10% in the control group to 5% in the intervention at 30 days. The randomisation and intervention will occur at the level of the patient’s nominated community pharmacy. Primary analysis will be a comparison of 30-day medication-related hospital readmissions between intervention and control clusters using a mixed effects Poisson regression model with a random effect for cluster (pharmacy) and a fixed effect for each step to account for secular trends. Trial registration This trial is registered with the Australian New Zealand Clinical Trials Registry: ACTRN12624000480583p , registered 19 April 2024.